2019
DOI: 10.2174/1381612825666190215123759
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Prostate Cancer and Metformin Consumption: A Systematic Review and Meta-analysis Study

Abstract: Introduction: Prostate cancer is the most common malignant cancer in men worldwide and after lung cancer, it is the second leading cause of cancer mortality in men. The purpose of this study was to investigate the relationship between prostate cancer and metformin consumption in men. Methods: The current study is a systematic and meta-analysis review based on the PRISMA statement. To access the studies of domestic and foreign databases, Iran Medex, SID, Magiran, Iran Doc, Medlib, ProQuest, Science Direct, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Metformin, which is the most commonly used as oral anti-diabetic drug in the world, has been reported to lower cancer incidence and cancer-specific death [103,104]. Epidemiological studies demonstrated that metformin improves survival of prostate cancer patients [105,106,107,108,109,110,111,112], and may reduce incidence of prostate cancer [112,113,114].…”
Section: Potential Effective Drugs and Diets For Preventing Progrementioning
confidence: 99%
“…Metformin, which is the most commonly used as oral anti-diabetic drug in the world, has been reported to lower cancer incidence and cancer-specific death [103,104]. Epidemiological studies demonstrated that metformin improves survival of prostate cancer patients [105,106,107,108,109,110,111,112], and may reduce incidence of prostate cancer [112,113,114].…”
Section: Potential Effective Drugs and Diets For Preventing Progrementioning
confidence: 99%
“…In this sense, experimental studies have found that this biguanide could have anti-ageing and anticancer effects through many actions 36 . Nevertheless, results are not uniform; in fact, recent meta-analyses reporting no association between duration of metformin use and PCa [37][38][39] have been shown to be affected by high heterogeneity and publication bias.…”
Section: Discussionmentioning
confidence: 98%
“…During the peer review process of this manuscript, Ghiasi et al [48] also summarized the relationship between prostate cancer and metformin consumption but only included 11 observational studies. Compared with these previous studies, our meta-analysis only included cohort and nested case–control studies and the results indicated that metformin use was not related with the incidence of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%